CONSIDERATION OF THE JUDGES AGAINST CRIMINAL CORRUPTION PERPETRATORS GRATIFICATION IN THE PROCESS OF AUCTION PROCUREMENT OF GOODS/SERVICES IN THE GOVERNMENT REGENCY OF PESAWARAN - Norma, Tria Dara; Seftiniara, Intan Nurina (Progressive Law Review, 2020)
Corruption impacts the state's financial losses and inhibits national development. As a result of the corruption crimes that occur so far in addition to the financial harm of the country or the country's economy, it also inhibits the growth and continuity of national development that demands high efficiency. The research methods used in this paper are juridical normative, and empirical approaches. The data used is secondary data and primary data. Data analysis using qualitative analysis of juridical. The judges were corrupt that the granting of criminal sanctions against gratuities had to be more severe because the defendant's actions were a form of error to be taken into account, no justification or excuse that eliminated criminal liability for the defendant. The judge must provide a fair criminal verdict for the defendant meaning that it is intended to provide a deterrent impact on the perpetrator of the crime, so as not to repeat the occurrence of the same crimes and expected for law enforcement officials especially judges in the sanction of defendants, judges can explore the legal values contained within the community. It is intended to create a sense of fairness towards society. It is expected that governments and academics and legal practitioners conduct periodic discussions/seminars to discuss attempts to address corruption.